Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pemasaran Kerajinan Mendong di Kota Tasikmalaya - Prama Permana; Siska Fajar Kusuma (Indonesian Journal of Strategic Management, 2023)
This study aims to the orientation of entrepreneurship to give a description market orientation, innovation and marketing performance and know the influence of entrepreneurship orientation, market orientation, and innovation influential and simultaneous partial evaluation of the performance of marketing a craftsman mendong in Tasikmalaya. Research methodology that is used is a method of descriptive and associative. Data used sourced from the primary data. Source of the primary data was obtained through the questionnaire a closed system with the question which has been provided the answer. The sample collection technique using purposive the sampling method of 173 business operators of a population that total about 305 business doers that his status is still active. Results of the research which is done by craftsmen show mendong in Tasikmalaya is quite good at interval between 52,01% to 68,00% with the average point of entrepreneurship orientation be 64,25%, 54,61% for the market orientation and 59,61% for innovation. It is better than the average value of the acquired 69,48% in 68,0% to 84,00%. The effects of such entrepreneurship orientation contribute as much as 21.8%, contributing to the market orientation 21,5%, and 11% to contribute as much as the performance of the craftsman mendong marketing in Tasikmalaya. Entrepreneurship Orientation, market orientation and innovation simultaneously influence significantly to be done by craftsmen the marketing of mendong in Tasikmalaya, the contributions provided by 54,3 %.